PENAFSIRAN QS. AL-FURQAN AAYT 67 RELEVANSINYA TERHADAP FINANCIAL MANAGEMENT DI ERA DIGITAL - lu'lu' ul maknun (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The rapid development of financial technology (fintech) has provided easy access to financial services, including online loans (pinjol). However, this convenience also raises serious academic and social issues related to the increasing dependence of the community on pinjol services which are often not in accordance with the principles of shariah finance. Therefore, it is necessary to conduct an in-depth study of financial management in the digital era in the context of online lending, especially through the perspective of the Qur'an, one of which is Surah Al-Furqan verse 67. This research uses a descriptive qualitative approach based on library research, focusing on analyzing the text of the Qur'an and contemporary interpretations and literature related to shariah financial management and studies on fintech. The purpose of this study is to identify the principles of shariah finance contained in Surah Al-Furqan verse 67 to understand the definition and procedures of online lending, as well as assess the practice of pinjol in terms of wisdom in financial management and the risks it poses. This principle is very relevant to be used as a foothold in addressing the rampant phenomenon of online loans so that people are not trapped in consumptive behavior and unproductive debt. This study has high relevance to the socio-economic conditions of the community, especially in facing major challenges in the digital era. The results of the analysis show the need for the development of shariah financial literacy that is adaptive to technological developments as well as offering practical solutions to manage finances ethically, wisely and effectively based on Islamic values.